Public Debt : The Brazilian Experience - Caputo Silva, Anderson (National Treasury, Brasilia, 2013)
The book analyzes the success of Brazil's public debt management practices. Over the past 10 years, Brazil has strengthened these practices so impressively that in early 2008, with the threat of a strong financial crisis in the world ahead, the main rating agencies assigned Brazil the investment grade. Despite the serious financial crisis that actually erupted in 2008, Brazil's credibility with domestic and international investors remains high. This book is organized into three parts: Part I, Understanding the Brazilian Public Debt; Origin and history of Brazil's public debt up to 1963, provides an historical and conceptual analysis of Brazil's public debt, exploring its main concepts and sustainability, and offering a view of its progress from its inception to the present. Part II, Managing the Brazilian Public Debt, describes all aspects of FPD management. Part III, The Public Debt Market in Brazil, describes how the public debt market operates in Brazil. It reviews recent developments and follows with the characteristics of public securities traditionally used to finance debt, along with their pricing schemes. Next, it describes the organization of Brazil's financial markets, the operation of primary and secondary debt markets, the expansion of the investor base over time and the main holders of government securities.